EFFICACY OF LOWER BACK MASSAGE FOR IMPROVEMENT OF LABOR PAIN AND PATIENT SATISFACTION - RANI, U; YAMEEN, S (Biological and Clinical Sciences Research Journal, 2024)
Labor pain management is crucial to obstetric care, as it influences the labor experience and overall patient satisfaction. Non-pharmacological interventions like lower back massage have been suggested to alleviate labor pain, but their efficacy requires further evaluation. Objective: To assess the efficacy of lower back massage in improving labor pain and patient satisfaction among pregnant women during labor. Methods: A prospective, cross-sectional study was conducted in the Gynecology and Obstetrics Department of Nishtar Hospital, Multan. A total of 160 pregnant women with single fetuses at full term, cervical dilation of 4 cm or more, and expected to have spontaneous delivery were included. Participants were divided into two groups: the study group (n=80) received sacral massage for 30 minutes at the end of the latent, active, and transition phases during contractions, while the control group (n=80) received standard care. Pain during severe contractions was measured using the Visual Analogue Scale (VAS), and patient satisfaction was rated on a scale from 1 to 10, with 10 being the most satisfactory. Data were collected through face-to-face interviews using a questionnaire. Statistical analysis was performed using appropriate tests, with significance at p<0.05. Results: Significant differences were observed between the groups in VAS scores during labor phases. In the latent phase, mean VAS scores were 4.9 ± 1 in the study group and 6.8 ± 1.5 in the control group (p<0.05). In the active phase, scores were 7.1 ± 2.0 and 9.4 ± 1.4, respectively (p<0.05). During the transition phase, the study group had a lower VAS score of 7.2 ± 3.2 compared to 9.5 ± 2.8 in the control group (p<0.05). The mean satisfaction score was significantly higher in the study group (9 ± 0.9) compared to the control group (7.4 ± 1) (p<0.05). Conclusion: Lower back massage significantly reduces labor pain and enhances patient satisfaction during labor. Massage in standard obstetric care is recommended to improve maternal comfort and labor outcomes.